2022
DOI: 10.2169/internalmedicine.8311-21
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 Antibody-positive Dermatomyositis with Rapidly Progressive Interstitial Pneumonia Presenting with Nephrotic Syndrome during Treatment with Corticosteroids and Cyclosporine

Abstract: A 50-year-old Japanese woman with anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5 antibody)-positive dermatomyositis presenting with rapidly progressive interstitial pneumonia was treated with corticosteroids and cyclosporine. She developed nephrotic syndrome during the treatment regimen with corticosteroids and cyclosporine. A kidney biopsy revealed a thrombotic microangiopathy (TMA) glomerular lesion. Anti-MDA5 antibody-positive dermatomyositis is prone to severe interstitial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In addition, CNIs, including tacrolimus and cyclosporine A, may hinder VEGF-mediated angiogenesis. Kawamoto et al [13] reported a case of DM patient who developed secondary thrombotic microangiopathy which may be associated with CNIs, although the association is considered to be low. Janus kinase (JAK) inhibitors are considered a therapeutic option for refractory DM.…”
Section: Ifn-related Biomarkersmentioning
confidence: 99%
“…In addition, CNIs, including tacrolimus and cyclosporine A, may hinder VEGF-mediated angiogenesis. Kawamoto et al [13] reported a case of DM patient who developed secondary thrombotic microangiopathy which may be associated with CNIs, although the association is considered to be low. Janus kinase (JAK) inhibitors are considered a therapeutic option for refractory DM.…”
Section: Ifn-related Biomarkersmentioning
confidence: 99%